(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Infertility is an increasingly prevalent condition which causes considerable psychological problems among infertile couples. Objective: To assess the psychological state of infertility in terms of depression, anxiety and stress among the infertile couples of Bangladesh. Materials and Methods: This cross-sectional study was conducted in the fertility centre of Combined Military Hospital, Dhaka from January to July 2018 among purposively selected 112 infertile couple. Data were collected by face to face interview through a pretested semi-structured Bangla questionnaire of Depression-Anxiety-Stress Scale and analyzed by computer software SPSS 19.0. Results: Among the 112 infertile couples, depression was found among 54.5%, anxiety among 53.6% and stress in 30.4% of females. Whereas among males depression was found in 38.4%, anxiety 26.8% and stress 21.4%. This study also revealed that couples with primary infertility had more depression, anxiety and stress than others. Conclusion: Females have been psychologically more affected than their husbands due to infertility. More than half of the females had depression and anxiety and about one third was affected by stress which was higher than their husbands. Journal of Armed Forces Medical College Bangladesh Vol.14(1) 2018: 41-45